Examining The Job Characteristics: The Influence of Employees Motivation And Leadership to Job Satisfaction - Ahmed S., Abdaladeam, Dr. Anton Agus Setyawan, SE., M.Si, M. Farid Wajdi, Ph.D (2014)
The purpose of this study was to analyze the influence of employee motivation and leadership on job satisfaction of employees at PT. Electricity Company of Government Persero (PLN) - UPJ Surakarta (Solo). Research is research with quantitative approach, by taking samples at PT. Electricity Company of Limited Government - UPJ Surakarta (Solo), it is located in Brigadir Jenderal Slamet Riyadi Street, No. 468 of Surakarta, Central Java, Indonesia. In this research, the writer gives the questionnaire to 60 people from 326 of population in PT. Electricity Company of Government Persero - UPJ Surakarta (Solo). The technique of collecting data using questionnaires. The data analysis technique used is multiple linear regression analysis. The results obtained showed that there is the influence of employee motivation on job satisfaction in PT. Electricity Company of Government Persero (PLN) - UPJ Surakarta (Solo); there is the influence of leadership on job satisfaction in PT. Electricity Company of Government Persero (PLN) - UPJ Surakarta (Solo); and there is the influence of employee motivation and leadership on job satisfaction in PT. Electricity Company of Government Persero (PLN) - UPJ Surakarta (Solo).